Associations of decreased serum total protein, albumin, and globulin with depressive severity of schizophrenia - Yin, Xu Yuan; Cai, Yuan; Zhu, Zhen Hua; Zhai, Chang Ping; Li, Jian; Ji, Cai Fang; Chen, Peng; Wang, Jing; Wu, Yi Ming; Chan, Raymond C. K.; Jia, Qiu Fang; Hui, Li (Frontiers in Psychiatry, 2022)
Objective: Depression and schizophrenia (SCH) were accompanied by an acute phase response (APR) that was implicated in the alterations in total protein (TP), albumin and globulin levels. The aims of this study are to examine serum TP, albumin and globulin levels, depressive symptom, their associations in SCH patients. Methods: Thirty-four SCH patients and 136 healthy controls (HCs) were recruited. Psychiatric symptoms and biomarkers were assessed using the PANSS as well as the bromocresol green and biuret methods. Results: Serum TP, albumin and globulin levels were lower in patients than those in HCs after adjusting for covariates (F = 46.11, P < 0.001; F = 31.69, P < 0.001; F = 12.48, P < 0.001). Serum TP and albumin levels were negative correlated with depressive score in patients (r = -0.37, P = 0.03; r = -0.37, P = 0.03). Stepwise multivariate regression analysis showed the negative associations of depressive score with serum TP, albumin and globulin levels in patients (β = -0.13, t = -2.92, P = 0.007; β = -0.23, t = -2.36, P = 0.03; β = -0.16, t = -2.40, P = 0.02). Serum TP, albumin and globulin levels exhibited the accuracies of 87.1%, 70.0% and 69.4% in discriminating between patients and HCs (AUC: 0.78, 0.68 and 0.77; sensitivity/specificity: 52.9%/95.6%, 55.9%/73.5% and 76.5%/67.6%). Conclusion: Our data suggested that decreased serum TP, albumin and globulin should be regarded as the SCH risk factors, and were implicated in the depressive severity of SCH, which further provided the support for hypothesis that SCH and depression were accompanied by the abnormal inflammatory cytokines with the APR.